Respuesta :
For a geometric sequence with first term a_1 = 5 and common ratio r = sqrt(3), the general formula for the nth term is:
a_n = (a_1)(r)^(n - 1)
In this case,
a_n = 5(sqrt3)^(n - 1)
a_n = (a_1)(r)^(n - 1)
In this case,
a_n = 5(sqrt3)^(n - 1)
Answer:
[tex]a_n = 5*(\sqrt{3}) ^{n-1}[/tex]
Step-by-step explanation:
The n-th term of a geometric sequence [tex]a_n = a_1r^{n-1}[/tex], where [tex]a_n[/tex] is the n-th term, [tex]a_1[/tex] is the first term, n is the number of terms.
Given:
[tex]a_1 = 5 ; r = \sqrt{3}[/tex]
Now plug in the given values in the n-th term formula, we get
Therefore, the general rule for n-th term of the sequence is [tex]a_n = 5*\sqrt{3} ^{n-1}[/tex]